A Semiotic Analysis of Political CaricatureCollected by Gatot Eko Cahyono - Narimo, Sabar (2012)
A political caricature is an illustration which is designed to communicate a social or political message. The objectives of the study are: (1) to find the relation between the index and the myths used in the caricature, (2) to identify the meaning of the index used in the caricature. The type of the study is qualitative interpretative type. The several steps are done to analyze the data. In analyzing the relation between the index and the myths used in the caricature, the steps are: analyzing the denotation level, analyzing the connotation level, and analyzing the myth. In analyzing meaning, the steps are: analyzing the signifier and analyzing the signified. The results of the study show that: (1) there are relations between the index and the myths used in caricature. From 15 data, there are 5 or 33, 33% the indexes are used based on the context in what time the caricature is made, 3 or 20% are used based on its function on daily life, 3 or 20 % are used based on the general assumption in society. Furthermore, there are 2 or 13, 33 % the indexes are used based on the official symbol, 1 or 6, 67% is used based on the party symbol and 1 or 6, 67 % is used based on the political terminology, (2) the meaning of the index used to represent the reality phenomena. From 15 data, there are 6 or 40% data referring to the political issues, 4 or 26, 67% data referring to the social issues, 3 or 20% data referring to the corruption issues, and 2 or 13, 33% data referring to the human right issues.